Inovasi Pembiayaan Sosial Syariah Untuk Meningkatkan Ketahanan Sosial Ekonomi Kota Bengkulu - Sari, Devi Permata; Pratami, Ego; Harpepen, Andi (Pakis Journal Institute, 2024)
Poverty is a major challenge in the economic development of Bengkulu Province. The high poverty rate in this province highlights the need for innovative approaches in Islamic social finance to enhance social and economic resilience. According to data from the Central Bureau of Statistics (BPS), the poverty rate in Bengkulu Province as of September 2022 was recorded at 14.34%, a decrease from the same period in the previous year, which was 14.43%. This study aims to analyze the role of innovative Islamic social finance, particularly through zakat, infaq, and sadaqah, in efforts to reduce poverty and improve social welfare in Bengkulu. Using a qualitative research method, this study presents Islamic social finance as a potential solution for improving the economic condition of society. The findings show that Islamic social finance can significantly contribute to reducing inequality and lowering poverty levels in Bengkulu, especially through social assistance programs such as the Basic Food Assistance Program (Program Sembako) and the Family Hope Program (PKH).